2004
DOI: 10.1159/000076538
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Growth Hormone Replacement Therapy on Pituitary Hormone Secretion and Hormone Replacement Therapies in GHD Adults

Abstract: Objective: We tested the impact of commencement of GH replacement therapy in GH-deficient (GHD) adults on the circulating levels of other anterior pituitary and peripheral hormones and the need for re-evaluation of other hormone replacement therapies, especially the need for dose changes. Methods: 22 GHD patients were investigated in a double-blind randomized study and 90 GHD patients in an open study at baseline and after 6 and 12 months of GH replacement therapy. Results: In the placebo-controlled trial, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 24 publications
(31 reference statements)
1
18
0
Order By: Relevance
“…Although the findings of Agha et al were comparable to those of previous reports, Hubina et al 1 reported that only 1 of 35 adults with organic hypopituitarism and severe GHD developed secondary hypothyroidism and the need to begin levothyroxine therapy during rhGH administration. In the same study, only 4 of 65 patients with secondary hypothyroidism who were receiving levothyroxine at the start of rhGH treatment required increases in levo thyroxine dosage during rhGH therapy.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Although the findings of Agha et al were comparable to those of previous reports, Hubina et al 1 reported that only 1 of 35 adults with organic hypopituitarism and severe GHD developed secondary hypothyroidism and the need to begin levothyroxine therapy during rhGH administration. In the same study, only 4 of 65 patients with secondary hypothyroidism who were receiving levothyroxine at the start of rhGH treatment required increases in levo thyroxine dosage during rhGH therapy.…”
Section: Resultssupporting
confidence: 72%
“…In patients with subclinical adrenocortico tropic hormone deficiency, therefore, administration of rhGH might unmask the need for cortisol replacement therapy. 1,5 …”
Section: Resultsmentioning
confidence: 99%
“…This effect is also seen in children with MHPD, but not in children with IGHD (81). The same mechanism may induce high FT 4 in a previously wellreplaced patient when GH treatment is started (80). Also to be considered is that both transdermal and oral estrogens increase thyroxin-binding globulin and patients may need higher L-T 4 replacement doses when these therapies are combined (75).…”
Section: Central Hypothyroidismmentioning
confidence: 99%
“…Therefore, careful monitoring of thyroid function is mandatory during GH treatment (78), as it may indicate changes in the T 4 dose needed. Patients with untreated GHD may have higher FT 4 levels than on GH replacement; GH therapy may, therefore, unmask undiagnosed CH (74,79,80). This effect is also seen in children with MHPD, but not in children with IGHD (81).…”
Section: Central Hypothyroidismmentioning
confidence: 99%
“…Studies suggest that rhGH may induce or unmask central hypothyroidism, or increase dose requirement for thyroid hormone among patients already receiving levothyroxine (in as many as 12-16% of patients) [3][4][5][6] . Proposed mechanisms include increased peripheral conversion of T4 to T3 by type I and II deiodinase 7,8 , increased thyroxine binding globulin (TBG) levels and subsequent lower free T4 9 , and decreased secretion of TSH per se 5,8 .…”
Section: Introductionmentioning
confidence: 99%